Engineering of Rocking Nut Maker Tools - Sulharman (IPTEK The Journal for Technology and Science, 2025)
There had been mechanically conducted an engineering of Rocking Nut Maker Tools for rocking nut small industry. The objective is to engineer a maker tool for rocking nut which can work with the assistance of motor without using manpower, thus it will increase the production of rocking nut. Making method on rocking nut maker tool includes: (1) Designing tool; (2) tool making; (3) Tool testing. According to the result of engineering tool, there were obtained: frame for tray that was made from angle iron: the height was 450 mm, the length was 1500 mm, and the width was 500 mm width, while the thickness was 3 mm. The tray was made from aluminium with 60 mm height, 1485 mm length, 485 mm width and 3 mm plate thickness. The motor had the power capacity of ½ HP, single phase and 1400 rpm while gearbox was 1:10. The wheels were made from iron with the diameter of 60 mm and the thickness of 20 mm. There are 4 wheels which were installed under the tray. Popper mechanism was made from iron that included iron plate with the diameter of 210 mm, the thickness of 7 mm and iron bar with the diameter of 15 mm and the length of 220 mm. This was equipped with speed variable. The result from tools performance could increase the production capacity by 400%; the bumpy texture on peanut surface could attach more strongly, the storage capacity increased for 6 months, while the production only lasted for 3 months if it was by manual. The capacity of rocking nut maker was 45 kg/day; it was only 7.5 kg/day by manual. The average time consumed for rocking nut making was 1.5 hours/ processing, while by manual was 3 hours/ processing. The rocking speed was 89-99rpm. This was an economical technology, by using this engineered tool, the production capacity per month was increased by 750 kg or equivalent with Rp. 47,250,000.- and by using this tool, there was an increase in profit of Rp. 13,450/ kg while by manual was only Rp 2,250/ kg. On the other side, the production cost by using tools was Rp 51, 550/kg, while by manual was Rp. 72.750/kg.